Upaya Meningkatkan Aktivitas Belajar Siswa melalui Model Pembelajaran Kooperatif Tipe STAD (Student Team Achevement Division) pada Tema 4 ‘Berbagai Pekerjaan’ Kelas IV UPT SPF SDN 101981 Galang - Muhammad Ulfa Yajie; Nila Lestari (Departement of Mathematics Education, 2024)
Based on the results of observations made in Class IV UPT SPF SDN 101981 Galang, student learning outcomes are still categorized as low. This is caused by several factors, one of which is the lack of use of models in learning. One alternative in solving this problem is to use a learning model that is appropriate to the implementation of good learning so that it can meet students' needs to be active and creative. Using the STAD model is an effective way to provide a variety of good learning atmospheres by creating a more effective atmosphere for discussion and collaboration so that it can motivate students to study harder. This research aims: (1.) To increase student learning activities through the STAD (Student Team Achevement Division) Cooperative Learning Model in Theme 4 'Various Jobs' class 4 UPT SPF SDN 101981 Galang. This research uses classroom action research (PTK) which is carried out in 2 cycles, where each cycle consists of 2 meetings. The data collection instrument is an observation sheet of teacher and student activities which is then analyzed using the average formula. The research results obtained were that in cycle I teacher activity was from 50 in the sufficient category, increasing in cycle II to 90 in the very good category. Student activity in cycle I was 60 in the moderate category, increasing in cycle II to 85 in the very good category. Student learning test results in cycle I were 41%, increasing in cycle II to 77%. Based on research, it can be concluded that the STAD (Student Team Achevement Division) Cooperative Learning Model is more active and student learning outcomes increase.